Status Hukum Pekerja Platform Digital Menurut Perspektif Hukum Ketenagakerjaan: Penelitian - Mutiara Safira Raudatul Hasanah; Agus Suprajogi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This studyexamines the legal status of digital platform workers in the context of an application-based economic transformation that increasingly dominates the Indonesian labor market. Although platform companies construct their arrangements as partnership relationships, the realities of work reveal algorithmic control, economic dependency, and operational regulations that closely resemble conventional employment relations. This research aims to analyze the legal position of platform workers under Law Number 6 of 2023 on Job Creation and to assess the effectiveness of labor protection principles as applied to this category of workers. Using a normative legal research method with statutory, conceptual, and interpretive approaches, the study finds that platform workers substantively fulfill the elements of an employment relationship, yet are not formally recognized as employees. As a result, they remain outside the scope of normative labor protections. This discrepancy between field realities and the existing legal framework generates legal uncertainty, shifts business risks onto workers, and leads to the non-fulfillment of basic labor rights guaranteed under Law Number 13 of 2003 on Manpower. The study recommends the development of minimum protection standards and the establishment of dispute resolution mechanisms tailored to the characteristics of digital labor.